Current status of clinician-educator tracks in internal medicine residency programmes. Issue 1143 (10th February 2020) - Daaboul, Yazan; Lin, Amy; Vitale, Kelly; Snydman, Laura K
ABSTRACT: Background: Residents in internal medicine programmes lack formal training in leadership, curriculum development and clinical teaching. Residency programmes created clinician-educator tracks (CETs) to formally teach residents to become effective educators and to involve them in the science of medical education. However, the curricula in these tracks are often locally developed and remain at the discretion of the individual programmes. Methods: This survey evaluates the frequency of CETs in internal medicine residency programmes in the USA and descriptively analyses their logistical and curricular content. During the academic year 2017–2018, directors of all Accreditation Council for Graduate Medical Education (ACGME) accredited internal medicine residency programmes in the USA were invited to participate in this survey (n=420). We developed a web-based 22-question survey to assess the logistics and curricular content of CET programmes. Results: A total of 150 programmes responded to the survey invitation (response rate=35.7%). Only 24% (n=36) of programmes offered a CET, the majority of which have been available for only 5 years or less. The track is most frequently offered to postgraduate year (PGY)-2 and PGY-3 residents. Only a minority of participating faculty (27.8%) have protected time to fulfil their CET role. Bedside teaching, feedback, small group teaching and curriculum development are the most commonly taught topics, and faculty mentorship and small group teaching methods are the most commonly used types of instruction. Conclusions: CETs are offered in only 24% of internal medicine residency programmes in the USA. The curricula of these tracks vary across programmes, and their success is often countered by logistic and financial challenges.